2020
DOI: 10.1097/md.0000000000022317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guizhi decoction for diabetic cardiac autonomic neuropathy

Abstract: Background: Diabetic cardiac autonomic neuropathy (DCAN) is one of the serious complications of diabetes. The pathogenesis of DCAN has not been fully elucidated. There is currently no effective treatment for such chronic disease. Traditional Chinese medicine has a long clinical history for the prevention and treatment of diabetes and chronic complications, and it also shows certain advantages in the treatment of DCAN. Many clinical studies have confirmed that Chinese medicine Guizhi decoction can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…GZD is wildly used to treat many internal diseases, including allergic or respiratory diseases, endocrine system disease, nervous system disease, and cardiac autonomic neuropathy [ 25 ]. Additionally, GZD has accumulated plentiful experiences in the treatment of cardiovascular diseases, such as hypertension [ 11 , 12 , 26 ]. However, its material basis and potential mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GZD is wildly used to treat many internal diseases, including allergic or respiratory diseases, endocrine system disease, nervous system disease, and cardiac autonomic neuropathy [ 25 ]. Additionally, GZD has accumulated plentiful experiences in the treatment of cardiovascular diseases, such as hypertension [ 11 , 12 , 26 ]. However, its material basis and potential mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that GZD significantly improved heart rate variability and vagus nerve activity, which are associated with the progression of hypertension [ 10 ]. A meta-analysis confirmed the beneficial effect and safety of GZD in the treatment of diabetic cardiac autonomic neuropathy [ 12 ]. Zheng et al reported that GZD associated formulas exerted significant effects on the attenuation of moderate-severe painful diabetic peripheral neuropathy [ 13 ].…”
Section: Introductionmentioning
confidence: 97%
“…Диабетическая кардиомиопатиявыраженное осложнение сахарного диабета. СД приводит к функциональным и структурным изме нениям сердца независимо от гипертонии, атеро склероза коронарных артерий или любого другого сердечного заболевания, и это подтверждает диа бетическую кардиомиопатию [7]. Одна из основ ных теорий причинности диабетической кардио миопатии -диабетическая нейропатия, которая приводит к симпатической денервации, изменя ющей кровоток миокарда, что влияет на его пер фузию и приводит к отсутствию загрудинной боли [8].…”
Section: особенности течения острого коронарного синдрома на фоне сахарного диабета второго типаunclassified